Enhanced pupillary light reflex in infancy is associated with autism diagnosis in toddlerhood - Nyström, P.; Gliga, T.; Jobs, E.; Gredebäck, G.; Charman, T.; Johnson, M.; Bolte, Sven; Falck-Ytter, T. (Macmillan Publishers Limited, 2018)
© 2018 The Author(s). Autism spectrum disorder (ASD) is a neurodevelopmental condition affecting around 1% of the population. We previously discovered that infant siblings of children with ASD had stronger pupillary light reflexes compared to low-risk infants, a result which contrasts sharply with the weak pupillary light reflex typically seen in both children and adults with ASD. Here, we show that on average the relative constriction of the pupillary light reflex is larger in 9-10-month-old high risk infant siblings who receive an ASD diagnosis at 36 months, compared both to those who do not and to low-risk controls. We also found that the magnitude of the pupillary light reflex in infancy is associated with symptom severity at follow-up. This study indicates an important role of sensory atypicalities in the etiology of ASD, and suggests that pupillometry, if further developed and refined, could facilitate risk assessment in infants.